Targeting tumor-infiltrating macrophages to combat cancer. (October 2013) - Panni, Roheena Z; Linehan, David C; DeNardo, David G
Tumor-associated macrophages are one of the major constituents of tumor stroma in many solid tumors and there is compelling preclinical and clinical evidence that macrophages promote cancer initiation and malignant progression. Therefore, these cells represent potential targets for therapeutic benefit. In this review, we will summarize macrophage phenotypic heterogeneity, the current understanding of how tumors take advantage of macrophage plasticity to generate immunosuppression, and how manipulation of specific macrophage populations can be used for therapeutic purposes through translational approaches.